Scheduling at a cross dock facility with stochastic truck arrival times - Karafa, Jeffery; Golias, Mihalis; Ivey, Stephanie; Saharidis, Georgios K.D.; Leonardos, Nikolaos (My University, 2012)
In this chapter we propose a game theoretic modeling framework based on the concept of Pareto optimality to schedule incoming trucks to the inbound doors of a freight distribution facility. We also attempt to address the issue of travel time variability from the truck's origin to the distribution facility. The problem is formulated as a bi-objective mixed integer programming problem. A combination of an Evolutionary Algorithms-based heuristic and a simulation-based Pareto front algorithm is proposed to solve the resulting problem and produce an optimized truck-to-door assignment. Numerical experiments indicate that the proposed truck scheduling approach provides improved schedules when compared to schedules that do not consider truck travel time variability. © 2012 by Nova Science Publishers, Inc. All rights reserved.